2012
DOI: 10.1029/2012jd017671
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurements of the seasonality of emission factors from savanna fires in northern Australia

Abstract: [1] Current good practice guidelines for national greenhouse gas inventories requires that seasonal variation in emission factors from savanna fires be considered when compiling national accounts. African studies concluded that the emission factor for methane decreases during the dry season principally due to curing of the fuels. However, available data from Australian tropical savannas shows no effect of seasonality on emission factors, consistent with observations that the fine fuels appear to cure fully soo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
123
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(136 citation statements)
references
References 38 publications
13
123
0
Order By: Relevance
“…These patterns are consistent with the trend of lower greenhouse gas emissions under early dry season fires, relative to late fires (Meyer et al, 2012) and point to the importance of available fuel load and its characteristics (greater herbaceous volume and lower moisture content late in the dry season) in understanding fire induced structural change in savannas. Murphy et al (2013) suggested that the moderation of fire regimes in northern Australia is likely to increase carbon storage 5 in woody biomass, but the extent to which woody biomass can increase in these savannas is highly uncertain.…”
Section: Fire Effects On Vertical Habitat Structuresupporting
confidence: 70%
See 1 more Smart Citation
“…These patterns are consistent with the trend of lower greenhouse gas emissions under early dry season fires, relative to late fires (Meyer et al, 2012) and point to the importance of available fuel load and its characteristics (greater herbaceous volume and lower moisture content late in the dry season) in understanding fire induced structural change in savannas. Murphy et al (2013) suggested that the moderation of fire regimes in northern Australia is likely to increase carbon storage 5 in woody biomass, but the extent to which woody biomass can increase in these savannas is highly uncertain.…”
Section: Fire Effects On Vertical Habitat Structuresupporting
confidence: 70%
“…There are widespread concerns that such fire regimes are linked to dramatic declines in faunal populations, through the removal of ground layer vegetation (Lawes et al, 2015;Legge et al, 2015;Woinarski et al, 2015). Methane and nitrous oxide emissions from savanna fires are included in Australia's national greenhouse-gas accounts, and are responsible for approximately 3% of total accountable greenhousegas emissions (Meyer et al, 2012). There is considerable interest in reducing the frequency and intensity of fires in northern ii) how vegetation structural diversity and carbon storage respond to increasing fire frequency; and iii) the structural impact of higher-intensity, late-season fires compared to early-season fires.…”
mentioning
confidence: 99%
“…Particular methodological challenges are to ensure that the application is supportive of local cultural practices and requirements, and that mitigating early dry season fire management activities actually reduce emissions-i.e. are conducted when fuels are fully cured rather than still being moist which would result in higher CH 4 emissions (Meyer et al 2012). A first step therefore is to work with local communities to assess the applicability of, and where practicable appropriately modify, the model.…”
Section: Implementation Challengesmentioning
confidence: 99%
“…An essential premise underlying Australia's recently developed savanna burning methodology (Russell-Smith et al 2009a;DCCEE 2012;Meyer et al 2012) is that reductions in fire frequency result in reduced GHG emissions because more of the fuel biomass (mostly grass and leaf litter) is decomposed biologically through pathways that, compared with savanna fires, produce lower relevant emissions per unit biomass consumed (Cook and Meyer 2009). In unburnt north Australian savannas, emissions of CH 4 and N 2 O arising from biological decomposition pathways are likely to be less than 10 % than that from fire (Cook and Meyer 2009;Jamali et al 2011).…”
Section: National Accounting and Project-scale Savanna Burningmentioning
confidence: 99%
“…In Australia approximately 550 000 km 2 of tropical and arid savannahs burn each year (Meyer et al, 2012;RussellSmith et al, 2007), representing 7 % of the continent's land area. In the tropical north of Australia, the fires during the early dry season in May/June consist of naturally occurring and accidental fires, as well as prescribed burns under strategic fire management practice to reduce the frequency and intensity of more extensive fires in the late dry season in October and November (Andersen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%